A survey of two-dimensional scheduling. (1st January 2014) - Shao, Hao; Xu, Rui; Tao, Feng; Chen, Huaping
In this paper, we present a literature review, classification schemes and analysis of methodology for scheduling problems on batch processing machine (BP) with both processing time and job size constraints which is also regarded as two-dimensional (TD) scheduling. Special attention is given to scheduling problems with non-identical job sizes and processing times, as well as the details of the basic algorithms, and related significant results.